Inventory of the family Orchidaceae in Desa Serdang village forest, Barusjahe, Karo, North Sumatra - Indri Aulya; Wina Dyah Puspita Sari; Yusran Efendi Ritonga (Bioma, 2024)
The village forest of Desa Serdang, Barusjahe, Karo, North Sumatra, is a community-managed forest. This forest exhibits a high species richness comparable to state-conserved and managed tropical rainforests. The orchid group is particularly important to assess in any area, as it generally indicates forest quality with good biodiversity levels. This study employs an exploratory method to reveal 32 orchid species, consisting of 16 terrestrial orchid species from 13 genera and 16 epiphytic orchid species from 11 genera. Descriptions and identification keys for each species are provided in this paper.